Application of linear vibration modeling of cross-ply composite plates with viscoelastic core. Issue 3 (8th May 2018) - Zhai, Yanchun; Liang, Sen
Abstract : Purpose: The purpose of this study is to facilitate the engineering technical personnel to easily choose the appropriate vibration analysis model in the design of symmetry composite sandwich structure with composite face layers and viscoelastic core. Therefore, the applicable condition of two linear vibration models was obtained by considering the vibration analysis of three-layered sandwich structures. Design/methodology/approach: Equilibrium equations of three kinds of vibration models were deduced using Hamilton's principle and were solved using the closed-form Navier solution. Then, numerical results were compared with those reported in the literature to verify the accuracy of the deduced calculating formulas. Findings: The applicable conditions of two linear vibration models are obtained by examining the influence of the ratio of length to total thickness (q) and that of viscoelastic thickness to total thickness (c) on the solutions. Two cases are considered about the applicable conditions of two linear vibration models based on the error analysis. Originality/value: The paper obtains the application conditions of two linear vibration models by using error analysis for the first time and provides the reference for engineering staff to easily choose a suitable vibration model to design a symmetry composite sandwich plate.